Observations Regarding On-Column, Flow-Induced Degradation During SEC Analysis - Striegel, André M. (Journal of liquid chromatography & related technologies, 2008)
The flow-induced degradation of ultra-high molar mass (M) polymers during their passage through a size-exclusion chromatography (SEC) column has been a subject of interest for several decades. Studies in this regard have been relatively few, however. Of interest is knowing whether degradation occurs in the interstitial medium, at the pore boundary, or both; whether the mechanism of degradation in the interstitial medium is the same as that at the pore boundary; and the types of flow fields involved in degradation, whether shear or extensional and, if the latter, what types of extensional flows are involved, transient or steady-state. Here, we attempt to shed some light on these topics by examining the SEC elution profiles of ultra-high M polystyrene standards. The standards have been analyzed at various flow rates, under conditions where the analyte either had access to both the interstitial volume and the pore volume or to only the interstitial volume. Results from these experiments were compared to each other, as well as to results from an ultrasonic degradation experiment where the analyte was depolymerized through the action of transient elongational flow fields. Results show that degradation occurs in both the interstitial medium and at the pore boundary and that the mechanisms of each of these are different from each other. While the degradation is almost assuredly due to extensional and not to shear flows, the former are either exclusively or predominantly steady-state, not transient.